Sulfur oxidation and implications for oxygen consumption in Base Mine Lake, the first pilot oil sands pit lake in the Athabasca oil sands region - Arrey, James L. S.; Yan, Yunyun; Colenbrander Nelson, Tara; Twible, Lauren E.; Zhang, Rui; Poulain, Alexandre J.; Warren, Lesley A. (Frontiers in Microbiology, 2025)
Base Mine Lake (BML) is the first pilot scale oil sands pit lake in the Athabasca Oil Sands Region (AOSR). Following a whole lake alum addition in September of 2016, a seasonally recurring zone of anoxia developed in the late summer hypolimnion of the BML water cap. The extent to which sulfur cycling exacerbates or mitigates this phenomenon in BML remains unclear. The objective of this 7–year was to characterize the identity and function of the sulfur oxidizing bacteria (SOB) and determine SOB risks to oxygen consumption in BML. The study revealed a persistent community of SOB that collectively encoded the genes involved in the primary sulfur oxidation pathways (Sox, rDSR, and S4I). The majority of SOB in BML have been previously identified as heterotrophs, allowing for metabolic flexibility depending on geochemical conditions that varied seasonally. The relative abundance of SOB genera comprising this community shifted as a result of the alum addition and has yet to stabilize over time. Simultaneous consumption of thiosulfate and nitrate was observed in the summer hypolimnion of BML post-alum, consistent with anaerobic sulfur oxidation. Furthermore, the anoxic zone occupied the largest portion of the hypolimnion when anaerobic sulfur oxidation was limited, suggesting it had a mitigating effect on anoxic zone expansion through removal of reduced sulfur species via nitrate driven sulfur oxidation by SOB. Constraining biological impacts to oxygen consumption in this pilot OSPL will be key to managing the growing tailings inventory of the AOSR as another ~23 OSPLs are proposed pending the outcome of BML.